Resistensi lalat rumah, Musca domestica Linnaeus (Diptera: Muscidae) dari empat kota di Indonesia terhadap permetrin dan propoksur - Intan Ahmad; Silvi Susanti; Kustiati Kustiati; Sri Yusmalinar; Resti Rahayu; Nova Hariani (Perhimpunan Entomologi Indonesia, 2015)
House flies (Musca domestica Linnaeus) is one of the common urban pests causing health, economics, and aesthetics problems. Although intensive control by using inseticides are carried out, there are reports of control failures, which are probably due to insect resistance. Bioassay tests with topical application to study the status as well as resistance mechanism of house flies collected from the city of Jakarta (JKT), Bandung (BDG), Yogyakarta (YGY) and Surabaya (SBY) to pyrethroid (permethrin) and carbamate (propoxur) insecticides were carried out. The results show that, as compared to the most susceptible strain (YGY), we found that BDG strain is highly resistant to permethrin with resistance ratio (RR) of 133.7 fold. SBY strain was the most resistant to propoxur with RR of 38.36 fold, followed by Bandung strain with RR of 18.22 fold. The addition of piperonyl butoxide (PBO) to either permethrin or propoxur in most of the strains caused a decrease in LD50 values and increasing the synergist ratio (SR) suggesting that the detoxifying enzyme mixed function oxidase (MFO) played an important role in the development of resistance to permethrin and propoxur. Our study is the first report of M. domestica resistance to permethrin and propoxur in Indonesia.